Proceso de atención de enfermería a paciente de 27 años con ovario poliquístico. - Jaime Camacho, Angie Leonor (2021)
This study aims to apply the knowledge acquired in nursing in the care of patients with a diagnosis of Polycystic ovary, it is taken into account that this type of syndromes are present in the female gender from the Puberty until menopause more frequently in women of childbearing age and is considered a pathology with a high number of cases despite the fact that there are patients who are asymptomatic and others who have mild or intense symptoms, which allow determining the existence of ovarian cysts and there is even the possibility that it grows to such an extent that it has cancer cells that endanger the life of the patient. These jokes usually have a diameter between 2 to 9 mm while statistics show that 4 out of 10 women of childbearing age suffer from this type of abnormalities during their reproductive age, most of them are usually accompanied by diagnoses related to obesity, hypertension and even insulin resistance develops and the appearance of acne; It is at that moment where the importance of generating a timely medical evaluation that allows determining the impact of the existing pathology is highlighted, as well as the proportion of information, establishment of guidelines and monitoring by the nursing professional that allows generating a prompt recovery to the patient.